2014
DOI: 10.1073/pnas.1324209111
|View full text |Cite
|
Sign up to set email alerts
|

Splice isoform and pharmacological studies reveal that sterol depletion relocalizes α-synuclein and enhances its toxicity

Abstract: Synucleinopathies are neurodegenerative diseases associated with toxicity of the lipid-binding protein α-synuclein (α-syn). When expressed in yeast, α-syn associates with membranes at the endoplasmic reticulum and traffics with vesicles out to the plasma membrane. At higher levels it elicits a number of phenotypes, including blocking vesicle trafficking. The expression of α-syn splice isoforms varies with disease, but how these isoforms affect protein function is unknown. We investigated two of the most abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Our data indicate that the presence of cholesterol in the lipid bilayer reduces the overall binding affinity for synapticlike vesicles, a result in agreement with studies in yeast showing that the inhibition of sterol synthesis enhances the vesicular localization of αS (Valastyan et al, 2014). A detailed analysis based on NMR CEST and relaxation experiments indicated that the structural effect of cholesterol on the membrane interaction by αS is restricted to residues in the NAC region, indicating a link between the overall binding affinity of the protein and the local interactions of the region 65-97.…”
Section: Discussionsupporting
confidence: 91%
“…Our data indicate that the presence of cholesterol in the lipid bilayer reduces the overall binding affinity for synapticlike vesicles, a result in agreement with studies in yeast showing that the inhibition of sterol synthesis enhances the vesicular localization of αS (Valastyan et al, 2014). A detailed analysis based on NMR CEST and relaxation experiments indicated that the structural effect of cholesterol on the membrane interaction by αS is restricted to residues in the NAC region, indicating a link between the overall binding affinity of the protein and the local interactions of the region 65-97.…”
Section: Discussionsupporting
confidence: 91%
“…If lipid rafts mediate synuclein localization in some functionally requisite fashion, perturbation of lipid rafts or of this association could lead to synuclein mislocalization and so contribute to disease [ 148 ]. In yeast, synuclein binds to lipid rafts [ 88 ] and inhibition of sterol synthesis led to decreased plasma membrane association by synuclein, increased (aberrant) vesicular association, and increased cellular toxicity [ 224 ]. Thus, higher membrane sterol concentrations favor plasma membrane binding of synuclein, though whether this is of functional or pathological relevance remains to be determined [ 224 ].…”
Section: Synuclein/membrane Interactions In the Multifaceted Pathologmentioning
confidence: 99%
“…In yeast, synuclein binds to lipid rafts [ 88 ] and inhibition of sterol synthesis led to decreased plasma membrane association by synuclein, increased (aberrant) vesicular association, and increased cellular toxicity [ 224 ]. Thus, higher membrane sterol concentrations favor plasma membrane binding of synuclein, though whether this is of functional or pathological relevance remains to be determined [ 224 ]. Finally, given the interactions between synuclein and fatty acids discussed above, it is of interest that PUFAs are able to directly promote synuclein oligomerization both in vitro and in vivo [ 180 , 198 ].…”
Section: Synuclein/membrane Interactions In the Multifaceted Pathologmentioning
confidence: 99%
“…The aggregation of AS was not enhanced when HEK239T cells were co-transfected with either 80% of AS140 or 20% of AS112 [ 136 ]. By contrast, another study carried out in a yeast model showed that, although expression of AS112 alone displayed marginal toxicity, the co-expression of both AS140 and AS112 enhanced the toxicity of AS140 [ 137 ].…”
Section: Snca Alternative Splicing and Its Rolementioning
confidence: 99%